Algorithms and complexity proceedings of the first Italian conference, Rome, Italy, 1-2 October 1990 - Ausiello, G. 1941-; Bovet, Daniel P.; Petreschi, Rossella 1950- (World Scientific, 2014)
"This proceedings contains contributions on topics such as the models of computation, analysis and design of sequential and parallel algorithms, data structures and their applications, approximating algorithms and probabilistic analysis, and computational complexity."--Publisher's description
Title from PDF title page (viewed on November 15, 2014). - "The first Italian Conference on Algorithms and Complexity will take place in Rome, Oct. 1-Oct. 2 1990"--Foreword
Keywords: Algorithms / Congresses; Computational complexity / Congresses; Electronic books